The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1103/physrevb.78.085306
|View full text |Cite
|
Sign up to set email alerts
|

Warming in systems with a discrete spectrum: Spectral diffusion of two-dimensional electrons in a magnetic field

Abstract: Warming in complex physical systems, in particular global warming, attracts significant contemporary interest. It is essential, therefore, to understand basic physical mechanisms leading to overheating. It is well known that application of an electric field to conductors heats electric charge carriers. Often an elevated electron temperature describes the result of the heating. This paper demonstrates that an electric field applied to a conductor with discrete electron spectrum produces a non-equilibrium electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 8 publications
1
19
1
Order By: Relevance
“…The effect, existing in a broad range of temperatures, can not be explained by an increase of the electron temperature due to the heating by the electric field E [11,54]. In the paper [11] the effect is attributed to a non-uniform spectral diffusion of the 2D electrons induced by the electric field [28].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The effect, existing in a broad range of temperatures, can not be explained by an increase of the electron temperature due to the heating by the electric field E [11,54]. In the paper [11] the effect is attributed to a non-uniform spectral diffusion of the 2D electrons induced by the electric field [28].…”
Section: Introductionmentioning
confidence: 97%
“…Despite the apparent applicability of the T e approximation to the overheated electron systems, recent studies have revealed an inadequacy of the temperature description of the nonlinear transport of highly mobile 2D carriers [11,52,54]. Instead of the T e approximation in this paper we use a different approach [28].…”
Section: Introductionmentioning
confidence: 99%
“…This effect, called quantal heating, does not exist in classical electron systems. The most essential property of quantal heating is the conservation of the total number of quantum states participating in the electron transport and, thus, the conservation of the overall broadening of the electron distribution 2,3 . In contrast to classical Joule heating, quantal heating leads to outstanding nonlinear transport properties of highly mobile 2D electrons, driving them into exotic nonlinear states in which voltage (current) does not depend on current 4 (voltage) 5 .…”
mentioning
confidence: 99%
“…Recently it was shown that the quantum properties of matter significantly affect the heating 1,2 , giving rise to a thermal stratification (quantization) of the electron distribution in energy space 3 . This effect, called quantal heating, does not exist in classical electron systems.…”
mentioning
confidence: 99%
“…At I dc > I th the differential resistance stays at zero value in a broad range of electric currents I dc > I th , significantly exceeding the threshold value I th . The initial drop of the resistance is associated with a quantal heating induced by the spectral diffusion of 2D electrons in crossed electric and magnetic fields [7][8][9][10] . The transition into the ZDR state is attributed to the local instability of the electric current at I dc > I th 11 .The local instability is considered to be the origin of another spectacular phenomenon -the zero resistance state observed in highly mobile 2D electron systems under a microwave irradiation [12][13][14] .…”
mentioning
confidence: 99%